Gas extraction hood modeling in a steel converter for energy recovery using phase change materials. (September 2022) - Ramirez, Roberto; Farias, Oscar
Highlights: Recovery of the residual energy from the exhaust gases of a steel plant. Continuous steam generation is achieved throughout the steel formation process. Transformation into electrical energy by means of the Rankine cycle. Use of phase change material in the forming gases of the steel decarburization process. Abstract: The steel industry is characterized by its energy-intensive processes. The steel forming process stands out, where the oxidation of carbon, when reacting, generates incomplete combustion gases at high temperature through the process basic oxygen injection in the furnace (BOF). A model of intermittent process and high temperature gas collection system is proposed and validated through experimental measurements. Through it, energy improvement opportunities are analyzed, highlighting energy recovery from high temperature flue gases by incorporating a phase change material (PCM) method for temporary energy storage. It was estimated that the fumes inside the hood could provide 77 GJ of available energy during the 15 min of oxygen injection (blowdown). With the use of a PCM device, between 13% and 32% residual energy recovery is obtained, equivalent to 10–25 GJ. In this way, a continuous heat flow could be generated during the whole process for steam generation through a cooling system in the gas collection system, with an electricity generation potential with a Rankine cycle of 14.5 MW.